PENGEMBANGAN MEDIA PEMBELAJARAN POWER POINT BERBASIS ISPRING SUITE 8 PADA TEMA PEDULI TERHADAP MAKHLUK HIDUP KELAS IV SDN 101886 KIRI HILIR TANJUNG MORAWA - Jurina Syafita (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This study aims to create learning media using software. The combination of Microsoft power point with Ispring will produce interesting media. The method used in this study is the development of Research and Development (R&D) by modifying the Brog and Gall development model through five stages including, potential and problems, data collection, product design, design validation, design revision and product testing. This study aims to (1) produce new products and find out the technique of developing learning media based on Ispring suite 8 through the development process. (2) To determine the feasibility level of Ispring suite 8-based learning media in science subjects. (3) To find out that the Ispring suite 8-based learning media is effective in increasing students' motivation and learning focus in class. The final result of this research is the development based on iSpring Suite 8 packaged in flash form. The results of the validation of media experts and material experts for Ispring suite 8 software development are feasible to be developed in the future. The percentage results obtained from media experts, namely 88.50% fall into the "very good" category, the percentage results obtained from material experts are 81.42 % into the "good" category, the percentage results obtained from effectiveness experts or learning experts are 93.07% fall into the "very good" category and the percentage results from product trials obtained as much as 86.09% fall into the "very good" category. This means that the Ispring suite 8-based learning media can be said to be feasible to be developed.